Secondary traumatization in refugee care - EMDR intervention for interpreters (STEIN): a study protocol for a quasi-randomized controlled trial - Rzepka-Marot, Irja; Kindermann, David; Friederich, Hans-Christoph; Nikendei, Christoph (Trials, 2024)
By the end of 2022, more than 100 million people worldwide fled their homes. Before, during and after their flight, refugees have high risk of experiencing traumatic events. Accordingly, around every third refugee is affected by posttraumatic stress disorder. For adequate mental health care, the service of interpreters is often urgently needed to overcome existing language barriers. However, repeated exposure with details of traumatic narratives, as experienced by interpreters, can be burdensome and can lead to trauma sequela symptoms in terms of secondary traumatic stress. Only few studies have examined the treatment of secondary traumatic stress to date. Based on the recommendations for the treatment of posttraumatic stress disorder with confrontational methods, this study was designed to evaluate the effectiveness of an eye movement desensitization and reprocessing (EMDR) intervention in a sample of interpreters working in refugee care suffering from secondary traumatic stress symptoms.